Improving Efficiency and Standardization in a Robotics Program: A Quality Improvement Project. (27th November 2018) - Price, Michael; Bates, Anne; Clagett, Michael
Abstract: After an evaluation of the growing robotics program at Christiana Care Health System in Newark, Delaware, perioperative leaders identified needs related to a lack of instrument set standardization and inconsistent workflow processes; these deficiencies were causing higher‐than‐anticipated turnaround time (ie, 59 minutes) and an excessive inventory of sterilized robotic instruments. A workgroup was created to review the results of the evaluation and develop solutions for the robotic surgery program. Goals included a 40‐minute procedure turnaround time and a 35% reduction in sterilized robotic instrument set inventory one year after project initiation. By developing a team training program, improving operational efficiencies, and improving standardization, the robotics program achieved a 10‐minute TAT reduction and a 54% reduction in sterilized robotic instrument inventory. Personnel considered the project to be a huge success because it laid the groundwork for improving efficiency and standardization in Christiana Care Health System's robotics program.